MATHEMATICS CONNECTION VIEWED FROM ADVERSITY QUOTIENT IN LMS ASSISTED PROBLEM BASED LEARNING IN SMA - Lilik Supono; Arief Agoestanto (USN Kolaka, 2023)
The connection between mathematics and adversity quotient (AQ) is vital in a person's ability to make decisions to solve problems in life. The problem-based learning (PBL) model, assisted by the learning management system (LMS), utilizes technology combining PBL models and LMSassisted learning. This study aims to (1) examine the effectiveness of LMS assisted PBL in improving high school students' mathematical connection skills and (2) examine the effect of AQ on students' mathematical connection abilities in LMS-assisted PBL learning. This type of research is a mixed-method research with a sequential explanatory design with a more significant quantitative portion than the qualitative one. The population ofthis study was class XI students of SMA N 1 Ungaran, Semarang Regency. The research sample was taken using a simple random sampling technique. Qualitative data was taken based on the students' AQ. Quantitative data analysis techniques with parametric statistics include average, classical completeness, and regression tests—qualitative data analysis techniquesusing data reduction, presentation, and conclusion. The results showed that (1) LMS-assisted PBL learning was effective in increasing students' mathematical connections, and (2) AQ had an influence on students' mathematical connection abilities in LMS-assisted PBL learning.